Co-developing patient and family engagement indicators for health system improvement with healthcare system stakeholders: a consensus study. Issue 2 (2nd February 2023) - Santana, Maria-Jose; Ahmed, Sadia; Fairie, Paul; Zelinsky, Sandra; Wilkinson, Gloria; McCarron, Tamara Lynne; Mork, Mikie; Patel, Jatin; Wasylak, Tracy
Abstract : Objective: To develop a set of patient and family engagement indicators (PFE-Is) for measuring engagement in health system improvement for a Canadian provincial health delivery system through an evidence-based consensus approach. Design: This mixed-method, multiphase project included: (1) identification of existing measures of patient and family engagement through a review of the literature and consultations with a diverse provincial council of patients, caregivers, community members and researchers. The Public and Patient Engagement Evaluation Tool (PPEET) was selected; (2) consultations on relevance, acceptability and importance with patient and family advisors, and staff members of Alberta Health Services' Strategic Clinical Networks. This phase included surveys and one-on-one semi-structured interviews aimed to further explore the use of PPEET in this context. Findings from the survey and interviews informed the development of PFE-Is; (3) a Delphi consensus process using a modified RAND/UCLA Appropriateness Method to identify and refine a core set of PFE-Is. Participants: The consensus panel consisted of patients, family members, community representatives, clinicians, researchers and healthcare leadership. Results: From an initial list of 33 evidence-based PFE-Is identified, the consensus process yielded 18 final indicators. These PFE-Is were grouped into seven themes: communication, comfort to contribute, support needed for engagement, impact and influence of engagement initiative, diversity of perspectives, respectful engagement, and working together indicators. Conclusions: This group of final patient, family and health system leaders informed indicators can be used to measure and evaluate meaningful engagement in health research and system transformation. The use of these metrics can help to improve the quality of patient and family engagement to drive health research and system transformation.